STRATEGI PENINGKATAN KUNJUNGAN WISATAWAN MELALUI OPTIMASI PEMASARAN WEBSITE DESA WISATA LAMAJANG DI KABUPATEN BANDUNG - Beata Winantya; Donni Junipriansa (ITB AAS Indonesia Surakarta, 2024)
Website Marketing is a marketing strategy that uses a site to introduce products and services owned by a business. Lamajang Tourism Village, one of the villages in Pangalengan District, Bandung Regency, utilizes the website www.desawisatalamajang.com for strategic marketing of village tourism potential through website marketing management. This research aims to find out how the marketing website management process in the Lamajang Tourism Village is a marketing strategy for the village's potential. This research uses a qualitative research design with a case study approach.. Data was collected through a process of observation, in-depth interviews, and documentation and then analyzed using the Miles, Sadana, and Huberman techniques The website marketing helped Lamajang Tourism Village to show its existence and gained more tourist than they had before. The management of website marketing is held by the special team which are consisting of IT Team and Tourism Awareness Group or called Pokdarwis. Website marketing help the tourist to find a lot of informations regarding the village and help them to decide better. Keywords : Website Marketing, Tourism Village.